2012
DOI: 10.1155/2012/498373
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Concentrated Ethanol Extracts of Edelweiss (Leontopodium alpinumCass.) Callus Cultures towards Human Keratinocytes and Endothelial Cells

Abstract: Edelweiss (Leontopodium alpinum Cass.) is traditionally employed in folk medicine as an anti-inflammatory remedy. In nature, the plant is sparsely available and protected; therefore production of callus cultures was established. A concentrated ethanolic extract of culture homogenate, with leontopodic acid representing 55 ± 2% of the total phenolic fraction (ECC55), was characterized for anti-inflammatory properties in primary human keratinocytes (PHKs) and endotheliocytes (HUVECs). Inflammatory responses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 39 publications
2
13
0
1
Order By: Relevance
“…Theoretically, SPMs could modify skin-UV interaction at several crucial points: (a) by absorption of UVA + UVB (screen action); (b) by inhibition of UV-induced free radical reactions in skin cells and extracellular matrix (scavenging and direct antioxidant chain-breaking effects); (c) by protection of skin surface lipid antioxidants, such as alpha-tocopherol, coenzyme Q10, and squalene (antioxidant rescue action); (d) by induction of endogenous antioxidant systems in keratinocytes and fibroblasts (indirect antioxidant effects); (e) by attenuation of inflammatory responses in cutaneous immune cells (keratinocytes/leukocytes/dendritic cells); (f) by modulation of excessive metabolic and proliferative UV-induced stress responses (anti-stress effects), and (g) by attenuation of UV-related immune suppression (immuno-modulation) [23,[78][79][80].…”
Section: Pre-selection Of Sun-protective Secondary Plant Metabolitesmentioning
confidence: 99%
“…Theoretically, SPMs could modify skin-UV interaction at several crucial points: (a) by absorption of UVA + UVB (screen action); (b) by inhibition of UV-induced free radical reactions in skin cells and extracellular matrix (scavenging and direct antioxidant chain-breaking effects); (c) by protection of skin surface lipid antioxidants, such as alpha-tocopherol, coenzyme Q10, and squalene (antioxidant rescue action); (d) by induction of endogenous antioxidant systems in keratinocytes and fibroblasts (indirect antioxidant effects); (e) by attenuation of inflammatory responses in cutaneous immune cells (keratinocytes/leukocytes/dendritic cells); (f) by modulation of excessive metabolic and proliferative UV-induced stress responses (anti-stress effects), and (g) by attenuation of UV-related immune suppression (immuno-modulation) [23,[78][79][80].…”
Section: Pre-selection Of Sun-protective Secondary Plant Metabolitesmentioning
confidence: 99%
“…Ex Stocks)) seems to have perspectives in the development of cosmeceutical treatments for acne vulgaris [159]. Anti-replicative senescence effects via sirtuin-dependent mechanisms have been reported for meristem cells of Leontopodium alpinum L. and Lippia citrobara L. [30,160]. The topical application of meristem cells from Syringa vulgaris provided skin healing and UV-protection [2,37,41,106] as well as anti-inflammatory and anti-microbial effects [30,41].…”
Section: Mechanisms Underlying Skin Ageing: Potential Targets For mentioning
confidence: 99%
“…For a long time, edelweiss has been used as traditional medicine against abdominal aches, bronchitis, diarrhea, dysentery, and fever [3,4]. Recently, several studies have shown the efficacy of edelweiss extracts for anti-inflammation in mice and rats [3] and human keratinocytes and endothelial cells [4].…”
Section: Introductionmentioning
confidence: 99%